Network security situation awareness based on indicators extracted - Xie, Zeqiang (2016)
Situation awareness refers to collect, process, and extract a variety of factors which can affect network situation awareness in the network environments, then build index system, establish evaluation model to assess the current network security situation awareness index and predict the future trend from the macro. Based on studying the predecessors' research works, the article regard the security events and network node resource information as the source of extracting index and construct a tree index system, combining with this system, it proposes a hierarchical network security situation assessment model, used fuzzy analytic hierarchy process (FAHP) to solve the problem of weight calculation among the model, designed Index calculation method for calculating network security situation index. Finally, it gives the design and implementation of a network security situation analysis prototype system.